2020
DOI: 10.2217/fca-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Process Optimization of Transfemoral Transcatheter Aortic Valve Implantation

Abstract: Background: The avoidance of prolonged hospital stay is a major goal in the management of transcatheter aortic valve implantation (TAVI) – medically and economically. Materials & methods: We compared the time range of the preprocedural length of stay in 2014/2015 with 2016/2017, after the implementation of the TAVI coordinator in 2016. This included restructured pathways for screening and pre-interventional diagnosis, performed examinations during the inpatient stay and major outcome variables. Results: Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…The role of the TAVI coordinator, therefore, did not impact the rate of repeat diagnostic procedures pre- and post-implementation. TAVI coordinator implementation at another German center significantly reduced the repetition of coronary angiography and CT examinations that had been performed at other facilities, however, there was no change in TEE examinations [ 9 ]. The differences between COORDINATE and the aforementioned study may, in part, be due to center/region-specific different practices and policies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The role of the TAVI coordinator, therefore, did not impact the rate of repeat diagnostic procedures pre- and post-implementation. TAVI coordinator implementation at another German center significantly reduced the repetition of coronary angiography and CT examinations that had been performed at other facilities, however, there was no change in TEE examinations [ 9 ]. The differences between COORDINATE and the aforementioned study may, in part, be due to center/region-specific different practices and policies.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of a TAVI coordinator could improve planning and workflow along the TAVI pathway, potentially shortening the treatment pathway [ 9 , 18 ]. The findings from the COORDINATE pilot study showed that TAVI coordinators had little impact on shortening time for diagnostics, admission, and the TAVI procedure itself.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations